Patristic spirituality: classical perspectives on ascent in the journey to God - Springer, Don W.; Clarke, Kevin M. (Studies in theology and religion, 2022)
"How does one grow holy in such times? This question drove the early Christian imagination no less than it does today. Patristic Spirituality: Classical Perspectives on Ascent to the Divine features numerous studies offering an "itinerary" for early Christian believers wishing to enter into the divine presence. Readers will discover an array of perennial early Christian wisdom into the practical challenges of ascent, "a work of God in Christ, transforming and incorporating us," says Lewis Ayres. See how early Christians cultivated the life of grace with hospitality, silence, almsgiving, and other ascetic practices for human elevation into mystical union with God. Contributors are: Benjamin D. Wayman, John S. Bergsma and Luke Iyengar, Hans Boersma, Stanley E. Porter, Gregory Vall Don W. Springer, Bogdan G. Bucur, Amy Brown Hughes, Sean Moberg, Stephen M. Hildebrand, Brian Matz, Anna Silvas, Ann Conway-Jones, Sandy L. Haney, Despina D. Prassas, Gerald Boersma, Brian E. Daley, Andrew Louth, Jonathan L. Zecher, Kevin M. Clarke, Lewis Ayres"--